A Novel Method of Human Adipose-Derived Stem Cell Isolation with Resultant Increased Cell Yield. Issue 6 (December 2016) - Tevlin, Ruth; McArdle, Adrian; Brett, Elizabeth; Chung, Michael T.; Paik, Kevin; Seo, Eun Young; Walmsley, Graham G.; Duldulao, Christopher R.; Atashroo, David; Zielins, Elizabeth; Vistnes, Stephanie; Chan, Charles K. F.; et al.
Abstract : Background: The authors have developed a novel protocol for isolating adipose-derived stem cells from human lipoaspirate. In this study, they compare their new method to a previously published standard protocol. Methods: Human adipose-derived stem cell isolation was performed using two methods to compare cell yield, cell viability, cell proliferation, and regenerative potential. The new and conventional isolation methods differ in two key areas: the collagenase digestion buffer constituents and the use of an orbital shaker. The osteogenic and adipogenic potential of adipose-derived stem cells isolated using both protocols was assessed in vitro, and gene expression analysis was performed. To assess the ability of the isolated cells to generate bone in vivo, the authors created critical-size calvarial defects in mice, which were treated with adipose-derived stem cells loaded onto hydroxyapatite-coated poly(lactic-co-glycolic acid) scaffolds. To test the ability of the isolated cells to enhance adipogenesis, the cells were added to lipoaspirate and placed beneath the scalp of immunocompromised mice. Fat graft volume retention was subsequently assessed by serial computed tomographic volumetric scanning. Results: The new method resulted in a 10-fold increased yield of adipose-derived stem cells compared with the conventional method. Cells harvested using the new method demonstrated significantly increased cell viability and proliferation in vitro ( p < 0.05). New method cells also demonstrated significantly enhanced osteogenic and adipogenic differentiation capacity in vitro ( p < 0.05) in comparison with the conventional method cells. Both cell groups demonstrated equivalent osteogenic and adipogenic regenerative potential in mice. Conclusions: The authors have developed a protocol that maximizes the yield of adipose-derived stem cells derived from lipoaspirate. The new method cells have increased osteogenic and adipogenic potential in vitro and are not inferior to conventional method cells in terms of their ability to generate bone and fat in vivo. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.